MAKNA PENGADEGANAN TOKOH FILM SUPERHERO DALAM VISUALISASI TOYS PHOTOGRAPHY (Tinjauan Estetis Karya Edy Hardjo) - Karyadi, Yatno (LAYAR: Jurnal Ilmiah Seni Media Rekam, 2018)
Toys photography is an art that integrates photography and other hobbies on toys. The models can be toys or dummies of well-known fictional figures like superheros. Artists of toys photography can arrange the toys in such a way that they may seem to act. The result can be photos of toys in action. The actions may contain some meaningful information. The action may tell certain stories related to toys as actors, attitude, expression, blocking, costumes, setting, and lighting. Edy Harjo is a photographer who chooses phenomeal and famous figures to make them look real. The result of this research shows that the meanings of the actions of the toys as superheroes in toys photography by Edy Harjo is different from the original meaning as shown in films. The aesthetic information contained in the actions includes new information, viewers’ assumption, and new meaning of the action. The photos are successful in communicating new ideas to the viewers. Edy Hardjo is also successful in obtaining the essence of this work, entertaining viewers, generating comicality, and new imagination.